Sulforaphane as a promising anti-caries agents: inhibitory effects on Streptococcus mutans and caries control in a rat model - Yu, Meijiao; Chen, Yu; Dong, Sishi; Chen, Zhongxin; Jiang, Xuelian; Wang, Yufei; Zhang, Linglin (Frontiers in Microbiology, 2025)
Dental caries has been one of the most prevalent diseases globally over the last few decades, threatening human oral and general health. The most critical aspect in caries control is to inhibit the dominant cariogenic bacteria Streptococcus mutans (S. mutans). Sulforaphane (SFN), a compound found in a wide range of cruciferous plants, has demonstrated bacteriostatic activities against various pathogenic bacteria. The objective of the present study was to investigate the effects of SFN on S. mutans though both in vitro and in vivo experiment. The minimum inhibitory concentration (MIC) against S. mutans was determined at 256 μg/mL. The growth of S. mutans and the biofilm formation were inhibited by SFN in a dose-dependent manner through suppressing the synthesis of extracellular polysaccharide (EPS) and acid production, as well as decreasing the acid tolerance. Meanwhile, SFN significantly weakened the cariogenic properties of S. mutans at sub-inhibitory concentrations, which were further illustrated by quantitative real-time PCR (qRT-PCR). Moreover, SFN were found to inhibit quorum sensing (QS) by downregulate comCDE system in S. mutans. Further investigation using a rat caries model displayed a prominent caries control in the SFN-treated group with no observed toxicity. The notable results demonstrated in this study highlight the potential of SFN as a natural substitute for current anti-caries agents, while also providing valuable insights into the potential applications of SFN in caries control.